Seroprevalence of Toxoplasma gondii and Neospora caninum in captive maned wolves (Chrysocyon brachyurus) from southeastern and midwestern regions of Brazil - Vitaliano, S. N.; Silva, DAO; Mineo, TWP; Ferreira, R. A.; Bevilacqua, E.; Mineo, JR (Elsevier B.V., 2004)
The main purpose of the present study was to investigate the occurrence of antibodies against T gondii and N. caninum in captive maned wolves from Brazil, considering that little information is available at the literature about infections by these parasites in this wild animal. Serum samples were obtained from 59 maned wolves originated from six zoos and from one ecological reserve of the southeastern and midwestern regions of Brazil. To detect IgG antibodies against T gondii, an ELISA protocol was used and the results were expressed as ELISA reactivity indexes (131). Serology for N. caninum was carried out by indirect fluorescent antibody test (IFAT) and cut-off titers were established at 1:25 dilution. From the total of the analyzed samples, 44 (74.6%) were seropositive for T gondii and only 5 (8.5%) for N. caninum. Seropositivity for T gondii ranged from 0 to 100% in the seven different origin locals, with rates over 50% among the six zoos, whereas no positivity was found in the samples from ecological reserve. For N. caninum, seroprevalence varied from 0 to 50% in the different locals, with the highest rates also detected in zoos. Seroprevalence for T gondii was strongly related with age, with rates significantly higher among adult wolves (91.7%) when compared to newborn or young animals. Seropositive samples for N. caninum were found predominantly in adult wolves. For both parasites, seroprevalence did not show a significant distinction in relation to gender. Although seroprevalence for T gondii was significantly higher when compared to N. caninum in the Brazilian captive maned wolves tested, these findings reflect the great exposure of this species to T gondii and, in lower extension, to N. caninum. Also, the present study demonstrated for the first time the presence of antibodies to N. caninum in wild life from South America. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; Neospora caninum; Chrysocyon brachyurus; maned wolf; antibodies